Molecular Targeting and Rational Chemotherapy in Acute Myeloid Leukemia - Pourrajab F; Zare-Khormizi MR; Hekmatimoghaddam S; Hashemi AS (Dove Medical Press, 2020)
Fatemeh Pourrajab,1,2 Mohamad Reza Zare-Khormizi,3 Seyedhossein Hekmatimoghaddam,4,5 Azam Sadat Hashemi4,6 1Nutrition and Food Security Research Centre, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 2Department of Clinical Biochemistry and Molecular Biology, School of Medicine, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 3School of Medicine, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 4Hematology & Oncology Research Center, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 5Department of Laboratory Sciences, School of Paramedicine, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 6Department of Pediatrics, School of Medicine, Shahid Sadoughi University of Medical Sciences, Yazd, IranCorrespondence: Seyedhossein HekmatimoghaddamDepartment of Advanced Medical Sciences and Technologies, School of Paramedicine, Shahid Sadoughi University of Medical Sciences, Yazd, IranTel +0098(913)3518314Email shhekmati2002@yahoo.comAzam Sadat HashemiDepartment of Pediatrics, School of Medicine, Shahid Sadoughi University of Medical Sciences, Yazd, IranTel +0098(913)1532465Email drazamhashemi@yahoo.comAbstract: Acute myeloid leukemia (AML) is a molecularly complex disease with multiple aberrant genetic pathways involved in its pathogenesis. Approximately one-third to one-half of patients with AML would relapse, and no standard therapy is established for relapsing and/or refractory AML (RR-AML) yet. It is unlikely that blockage of only one specific pathway will lead to prolonged remissions and cures in all fractions of the AML patients population. Nowadays, novel therapeutic agents with rational combination are being recognized which improve the cure rate for relapsed AML. These drugs and their metabolites impart unique properties in the interaction with each of the intracellular targets and metabolic enzymes whereby resulting in unique clinical activity. To date, most of the combinations have used a targeted agent combined with standard agents such as anthracyclines, cytarabine, or hypomethylating agents to improve the outcome. Rational combinations of DNA damage-inducing therapies with DNA methyltransferase and histone deacetylase inhibitors synergistically enhance the DNA damage, growth inhibition and apoptosis of myeloid cells. This review makes a thorough look at current antineoplastic agents for AML with emphasis on its genetics and molecular mechanisms of action and the role of combination regimens.Keywords: antineoplastic agents, drug therapy, combination, genetics, leukemia, myeloid, acute, molecular targeted therapy